Differential gene expression during substrate probing in larvae of the Caribbean coral Porites astreoides. Issue 22 (29th October 2019) - Walker, Nia S.; Fernández, Rosa; Sneed, Jennifer M.; Paul, Valerie J.; Giribet, Gonzalo; Combosch, David J.
Abstract: The transition from larva to adult is a critical step in the life history strategy of most marine animals. However, the genetic basis of this life history change remains poorly understood in many taxa, including most coral species. Recent evidence suggests that coral planula larvae undergo significant changes at the physiological and molecular levels throughout the development. To investigate this, we characterized differential gene expression (DGE) during the transition from planula to adult polyp in the abundant Caribbean reef‐building coral Porites astreoides, that is from nonprobing to actively substrate‐probing larva, a stage required for colony initiation. This period is crucial for the coral, because it demonstrates preparedness to locate appropriate substrata for settlement based on vital environmental cues. Through RNA‐Seq, we identified 860 differentially expressed holobiont genes between probing and nonprobing larvae ( p  ≤ .01), the majority of which were upregulated in probing larvae. Surprisingly, differentially expressed genes of endosymbiotic dinoflagellate origin greatly outnumbered coral genes, compared with a nearly 1:1 ratio of coral‐to‐dinoflagellate gene representation in the holobiont transcriptome. This unanticipated result suggests that dinoflagellate endosymbionts may play a significant role in the transition from nonprobing to probing behaviour in dinoflagellate‐rich larvae. Putative holobiont genes were largely involved in protein and nucleotide binding, metabolism and transport. Genes were also linked to environmental sensing and response and integral signalling pathways. Our results thus provide detailed insight into molecular changes prior to larval settlement and highlight the complex physiological and biochemical changes that occur in early transition stages from pelagic to benthic stages in corals, and perhaps more importantly, in their endosymbionts.